(3JHjGf MbjbI ePgH GdEeGejIs - (3CHh GdMSf GdYGfdj GdfLajs
(3ChdgG (B:s
(3GdMeO ddg (B.. (3gPG eNJUQ eajO aj JHjGf MbjbI ePgH GdEeGejI GdeJeScjf HCFeI GdWGFaI GddEKfi YTQjI hjhVM eG Ydjg CSGSg GdPj ef eGd Yfg Vd (B...s
(3BNQgG (B:s
... (3aCNHQhfj Gfg ONd Edi GdMeGe Edi MhV ajg eGA MGQ aZTj Ydjg heGJ ajg hCeKGd eG PcQfGg cKjQI hcai gPG dUGMH GdHUjQI (B... (3gPG BNQ eG CQOfG EjQGOg gfGs
(3Yf fSNI HNW GdeDda (B- (3aj GdHWGbI GdfGSN (B: (3TjQ Hf eMeO GdMhjRj GdehShjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds